Systematic literature review and critical success factor analysis to determine a model’s implementation elements - Ismail, S.; Marjudi, S.; Wan Hassan, W. A. S.; Raja Lope Ahmad, R. M. T.; A A Md Kassim, A. A.
Model implementation is a tedious process. The theoretical studies of a concept and its implementation are quite challenging. One of the biggest challenges is to identify a model’s elements, especially when it involves integrating two or more complex and dynamic fields into one combined model. This research aims to identify the implementation elements of a shariah compliant business analytics model called Halal Supply Chain Management Transactions (HSCMT) Model. This research used Systematic Literature Review (SLR) in order to qualitatively analyse the Critical Success Factor (CSF) of HSCMT, which produced the HSCMT Model implementation elements. The CSF Analysis results showed that there were 19 related CSF elements with emphasis of 57.9% on external factors and 89.5% on buildingadapting factors. Results also showed that the most important aspect of HSCMT were environmental factors, followed by factors of SME owners and their organization, the Halal industry, and lastly the role of financial institutes. This proves that both SLR and CSF can be used as integration tools in identifying a model’s implementation element, thus improving data collections method for models when researching in a movement constraint period such as during a pandemic outbreak.